Security and Privacy : Global Standards for Ethical Identity Management in Contemporary Liberal Democratic States - John Kleinig; Peter Mameli; Seumas Miller; Douglas Salane; Adin Schwartz (ANU Press, 2011)
This study is principally concerned with the ethical dimensions of identity management technology – electronic surveillance, the mining of personal data, and profiling – in the context of transnational crime and global terrorism. The ethical challenge at the heart of this study is to establish an acceptable and sustainable equilibrium between two central moral values in contemporary liberal democracies, namely, security and privacy. Both values are essential to individual liberty, but they come into conflict in times when civil order is threatened, as has been the case from late in the twentieth century, with the advent of global terrorism and trans-national crime.We seek to articulate legally sustainable, politically possible, and technologically feasible, global ethical standards for identity management technology and policies in liberal democracies in the contemporary global security context. Although the standards in question are to be understood as global ethical standards potentially to be adopted not only by the United States, but also by the European Union, India, Australasia, and other contemporary liberal democratic states, we take as our primary focus the tensions that have arisen between the United States and the European Union.